Metabolic engineering of Bacillus subtilis for l‐valine overproduction. Issue 11 (25th September 2018) - Westbrook, Adam W.; Ren, Xiang; Moo‐Young, Murray; Chou, C. Perry
Abstract: Bacillus subtilis has been commonly applied to industrial enzyme production due to its genetic tractability, "generally recognized as safe (GRAS)" status, and robust growth characteristics. In spite of its ideal attributes as a biomanufacturing platform, B. subtilis has seen limited use in the production of other value‐added biochemicals. Here, we report the derivation of engineered strains of B. subtilis forl ‐valine overproduction using our recently developed CRISPR (clustered regularly interspaced palindromic repeats)‐Cas9 (CRISPR‐associated [protein] 9) toolkit. We first manipulate the nativel ‐valine biosynthetic pathway by relieving transcriptional and allosteric regulation, resulting in a >14‐fold increase in thel ‐valine titer, compared to the wild‐type strain. We subsequently identify and eliminate factors limitingl ‐valine overproduction, specifically increasing pyruvate availability and blocking the competingl ‐leucine andl ‐isoleucine biosynthetic pathways. By inactivating (a) pdhA, encoding the E1α subunit of the pyruvate dehydrogenase complex, to increase the intracellular pyruvate pool, and (b) leuA and ilvA, respectively encoding 2‐isopropylmalate synthase andl ‐threonine dehydratase, to abolish the competing pathways, thel ‐valine titer reached 4.61 g/L in shake flask cultures. Our engineeredl ‐valine‐overproducing strains of B. subtilis are devoid of plasmids and do not sporulate due to the inactivation of sigF, encoding the sporulation‐specific transcription factor σ F, making them attractive for large‐scalel ‐valine production. However, acetate dissimilation was identified as limitingl ‐valine overproduction in Δ pdhA B. subtilis strains, and improving acetate dissimilation or identifying alternate modes of increasing pyruvate pools to enhancel ‐valine‐overproduction should be explored. Abstract : We have engineered Bacillus subtilis for L‐valine overproduction using our recently developed CRISPR‐Cas9 toolkit. L‐valine production was increased by more than 46‐fold by 1) relieving transcriptional and allosteric regulation naturally inhibiting L‐valine biosynthesis, 2) increasing cellular pyruvate pools, and 3) abolishing competing branched‐chain amino acid biosynthesis pathways. As a result, we have created an industrially relevant platform for microbial amino acid production, while providing new insight into branched‐chain amino acid biosynthesis in this model organism.